Interstitial Lung Disease and Myositis in a Patient With Antisynthetase Syndrome and PL12 and Ro52 Co-positivity in a Retired Medical Officer. Issue 7 (1st July 2021) - Loncharich, Michael F; Anderson, Caleb W; Collins, Jeannette; Edison, Jess
Abstract: Antisynthetase syndrome (ASS) is an idiopathic inflammatory myopathy characterized by myositis, arthritis, interstitial lung disease (ILD), Raynaud's phenomenon, and distinctive cutaneous manifestations. Anti-PL12 is a rare myositis-specific autoantibody classically associated with an amyopathic presentation and rapidly progressive ILD. Anti-Ro52 is a myositis-associated antibody that has been postulated to be directly pathogenic in inflammatory myopathy patients. The disease phenotype, course, and response to treatment associated with anti-PL12 and anti-Ro52 co-positivity is not well described. A 58-year-old man with anti-PL12 and anti-Ro52 ASS presented with rapidly progressive ILD and myositis refractory to high-dose prednisone. He ultimately required a dexamethasone burst with intravenous immunoglobulin and mycophenolate mofetil for disease control. Severe and rapidly progressive myositis is infrequently reported in anti-PL12 ASS. This case suggests that concurrent anti-Ro52 positivity predicts a more aggressive disease phenotype and may require more initial immunosuppression. If rapid progression of this disease were to occur in an active duty service member, it would have significant implications for readiness and potentially catastrophic outcomes in the deployed setting. Early identification and treatment of the disease are imperative. The question must also be raised of an occupational exposure from military service.